1936
DOI: 10.1017/s0022172400043710
|View full text |Cite
|
Sign up to set email alerts
|

Notes On The Vi Antigen Of Bacillus Typhosus

Abstract: a series of sporadic cases of enteric fever in Khartoum during the latter part of 1934 and 1935 afforded an opportunity of examining certain claims advanced in these papers. As the following observations on various aspects of the subject have been carried out over a period of 18 months the results are inevitably somewhat scrappy, but in view of the importance of the subject it was thought that they might not be altogether without interest for other workers.As a strictly chronological record would be somewhat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1937
1937
1952
1952

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…SINCE the description of the new typhoid Vi antigen and its corresponding antibody by Felix and his co-workers, various studies have appeared on this subject confirming their observations (Kauffmann, 1935a, b;Dyachenko, 1936;Horgan, 1936;Craigie & Brandon, 1936a, b;Robertson & Yu, 1936;Almon & Stovall, 1936;Bensted, 1937;and others). The presence of Vi antigen in a typhoid strain can be inferred from its 0 inagglutinability and confirmed by agglutinating it against a pure Vi serum.…”
Section: From the Deccan District Laboratory Trimulgherry Indiamentioning
confidence: 73%
See 1 more Smart Citation
“…SINCE the description of the new typhoid Vi antigen and its corresponding antibody by Felix and his co-workers, various studies have appeared on this subject confirming their observations (Kauffmann, 1935a, b;Dyachenko, 1936;Horgan, 1936;Craigie & Brandon, 1936a, b;Robertson & Yu, 1936;Almon & Stovall, 1936;Bensted, 1937;and others). The presence of Vi antigen in a typhoid strain can be inferred from its 0 inagglutinability and confirmed by agglutinating it against a pure Vi serum.…”
Section: From the Deccan District Laboratory Trimulgherry Indiamentioning
confidence: 73%
“…The explanation would appear to be the unsuitability of Lab Lemco and other meat extracts as nutrient agents for the routine growth of the organisms of this group. The deleterious effect of such artificial media on the antigenic complex of the highly virulent strains of typhoidparatyphoid group has already been commented on by various observers (Horgan, 1936;Bhatnagar et at. 19376;Bensted, 1937).…”
Section: Average Lethal Dose and Protective Powermentioning
confidence: 92%
“…Gundel & Abdoosh (1936) had 1 positive of very low titre (1:10) amongst 21 typhoid sera, and 1 good positive amongst 11 convalescents. In 100 normal sera Horgan (1936) found traces in a serum dilution of 1: 10 six times only, and in 28 typhoid patients, by means of repeated examinations, Vi agglutinin was found in a small number only. Our own observations on Vi agglutinins in patients and convalescents are rather similar to those quoted.…”
Section: The Agglutinins Of Typhoid Carriersmentioning
confidence: 93%
“…Early work with heat-killed cultures failed to demonstrate Vi agglutinin production in rabbits, but with refinement in methods of detecting the antibody we have found it in some of our rabbit antisera, and Horgan (45) reports it also. Early attempts to demonstrate the antibody in human sera following vaccination likewise failed (10,24); but unpublished results of work at this laboratory have shown that if blood is drawn at the right time, such vaccinated individuals may sometimes reveal it.…”
mentioning
confidence: 86%